Assistance from „A” to „Z” – Professional activation of homeless people from Wroclaw Circle St. Brother Albert Aid Society. D4.2 Deliverable, Evaluation report on case study - Wiktorska-Święcka, Aldona; Moroń, Dorota (European Commission)
The report presents the results of the case study evaluation. The subject of the case study is the program Assistance from A to Z – Professional activation of homeless people from Wroclaw Circle St. Brother Albert Aid Society. The project was implemented in the period of time: 30.09.2012-30.10.2015 in Wroclaw by Wroclaw Circle St. Brother Albert Aid Society. The project concerns the socio-professional activation of people at risk of social exclusion; hence it is a part of social inclusion of people at risk of social exclusion policy. It applies to a specific group of people at risk of exclusion - the homeless – and is an investment for activation and empowerment them. Assistance from A to Z project was implemented under the Human Capital Operational Programme and was financed by the European Social Fund. The report contains: literature review, needs assessment, theory of change, process evaluation, impact evaluation and economic evaluation using the SROI method. The evaluation of the project allowed demonstrating that it is an innovative social investment and use of innovative methods of accompaniment was the key success factor of the project.
Keywords: social innovation; social investments; social and professional activation; homelessness; accompaniment method